Point-Counterpoint: Can Newly Developed, Rapid Immunochromatographic Antigen Detection Tests Be Reliably Used for the Laboratory Diagnosis of Influenza Virus Infections? - Dunn, James J. (J Clin Microbiol, 2015)
Five years ago, the Point-Counterpoint series was launched. The initial article asked about the role of rapid immunochromatographic antigen testing in the diagnosis of influenza A virus 2009 H1N1 infection (D. F. Welch and C. C. Ginocchio, J Clin Microbiol 48:22–25, 2010, http://dx.doi.org/10.1128/JCM.02268-09). Since that article, not only have major changes been made in immunochromatographic antigen detection (IAD) testing for the influenza viruses, but there has also been rapid development of commercially available nucleic acid amplification tests (NAATs) for influenza virus detection. Further, a novel variant of influenza A, H7N9, has emerged in Asia, and H5N1 is also reemergent. In that initial article, the editor of this series, Peter Gilligan, identified two issues that required further consideration. One was how well IAD tests worked in clinical settings, especially in times of antigen drift and shift. The other was the role of future iterations of influenza NAATs and whether this testing would be available in a community hospital setting. James Dunn, who is Director of Medical Microbiology and Virology at Texas Children's Hospital, has extensive experience using IAD tests for diagnosing influenza. He will discuss the application and value of these tests in influenza diagnosis. Christine Ginocchio, who recently retired as the Senior Medical Director, Division of Infectious Disease Diagnostics, North Shore-LIJ Health System, and now is Vice President for Global Microbiology Affairs at bioMérieux, Durham, NC, wrote the initial counterpoint in this series, where she advocated the use of NAATs for influenza diagnosis. She will update us on the commercially available NAAT systems and explain what their role should be in the diagnosis of influenza infection.